1990
DOI: 10.1021/j100367a068
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic effect in symmetrical cells of a liquid crystal porphyrin

Abstract: the organizing element which promoted complex formation was the polymer, to which pyrochlorophyll was bound by ligation and DTNB by counterion attraction. In the present case, the organizing element is evidently the cationic micelle.Chl and its relatives have been examined in almost every conceivable kind of model system in efforts to imitate photosynthesis. To our recollection, however, this is the first report of its presence in cationic inverted micelles. Chl has been reported in anionic inverted micelles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
166
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(183 citation statements)
references
References 6 publications
16
166
0
1
Order By: Relevance
“…We therefore assume that the overall conductivity is determined by the integral of the local resistivity ͑determined by the local photocarrier concentrations͒, rather than averaging the total amount of formed photocarriers over the total film thickness as is the case for high mobilities. Analogue to Gregg, Fox, and Bard, 30 we deduce for the conductivity…”
Section: ͑12͒supporting
confidence: 69%
See 1 more Smart Citation
“…We therefore assume that the overall conductivity is determined by the integral of the local resistivity ͑determined by the local photocarrier concentrations͒, rather than averaging the total amount of formed photocarriers over the total film thickness as is the case for high mobilities. Analogue to Gregg, Fox, and Bard, 30 we deduce for the conductivity…”
Section: ͑12͒supporting
confidence: 69%
“…The explanation is thus found in the very low mobility of carriers in organic materials. 17,18,30 A value as low as 8 ϫ10 Ϫ9 cm 2 /V s for the effective mobility is inferred by Savenije and co-workers 24 from measurements of the diffusion coefficient of carriers in the porphyrin polymer films.…”
Section: ͑13͒mentioning
confidence: 94%
“…There was a belief that a single homogeneous film without any asymmetry would not show photogenerated electron-hole separation. In fact, it did, because of differential rates at the interfaces, but the efficiency was not good (47). We later showed that if one applied an electrical field to the film during the cooling stage, the photocurrent was much improved, at least initially (48).…”
Section: Miscellaneous Other Studiesmentioning
confidence: 96%
“…Gregg et al 74 and Petritsch et al 75 were the first ones to demonstrate the PV effect in porphyrin-and Pc-based DLCs. However, the seminal work of Schmidt-Mende et al 6 on well-defined discotic PV solar cell prepared from a hexa-perihexabenzocoronene (HBC)-based DLC, reported in 2001, generated tremendous interest in this field.…”
Section: Liquid Crystals In Photovoltaics M Kumar and S Kumarmentioning
confidence: 99%